Analysis of The User Experience of a Mobile Application System : A Case Study of Xyz - Firstama, Panjinagara Vandy; Galinium, Maulahikmah; Purnama, James (Journal of Applied Information, Communication and Technology, 2017)
This research intention is to comparing user experience value of mobile applic ation using User experience(UX) result from new and old sys tem, then doing gap analysis to determine how much improvement of user experience in the new system compared to old system. By using User Experience Questionnaire (UEQ), this research is to evaluat e which aspect of mobile application is looked for by its u ser. Survey is conducted to 60 people to answer what experience they have on old application, new application and user expectation for application and compare them. The result shows that there s mu ch improvement from old application to new application, and for expectation user towards new and old application, the gap between new app to expectation become closer if compare with old app to expectation